(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2017)
Abstract | When Minor Threat sang “I’ve got straight edge” back in the 1980s they could not imagine the proportions the straight edge message would achieve in a few years. In São Paulo, the straight edge subculture was consolidated in the 1990s around a collective and its festival Verdurada, which is still active. The dynamics to establish the boundaries of the straight edge identity are complex, usually dealing with several visual aspects. This work aims to shed light onto the visuality of the straight edge subculture and the Verdurada, discussing the place(s) that straight edgers occupy in the 21st century. Résumé | Lorsque le groupe Minor Threat chanté « I’ve got straight edge » dans les années 1980, il ne pouvait pas imaginer les proportions que le message straight edge pourrait atteindre. À São Paulo, le straight edge sous-culture a été consolidée dans les années 1990 autour du festival Verdurada et son collectif homonyme, qui est toujours actif. La dynamique d’établir les limites de l’identité straight edge est complexe, généralement constitué par plusieurs aspects visuels. Ce travail vise à analyser la visualité de la sous-culture straight edge et la Verdurada, en discutant la place qui les straight edgers occupent dans le 21e siècle.